Case study of the London 2012 Olympic and Paralympic pharmacy service preparations. (13th October 2014) - File, Hayley; Thomas, Trudy; Anderson, Geoff
Abstract: Objectives: The Pharmacy Clinical Services Group (PCSG) was formed in 2009. Its aim was to design and deliver a world-class pharmacy service to 250 000 accredited persons and consider the pharmaceutical needs of 9.2 million visitors to the London 2012 Games. Methods: The explanatory case study method was used to investigate how the PCSG prepared and how they considered the wider vision of the Games. The study investigated two propositions: (1) that the PCSG has a communication function and (2) that it has a design function. A range of data were examined using NVivo 9 data management software. Key findings: The study identified four emerging themes and a number of subthemes. Conclusions: The study validated the propositions and highlighted that the PCSG had a leading role within the wider multidisciplinary team. The study found that the PCSG embraced the wider vision of the Games and was exceptionally well prepared to deliver a world-class pharmacy service, anticipating a new gold standard for the provision of pharmacy services for future sporting events.